Penyuluhan Tanaman Kunyit dan Pacar Air Sebagai Alat Deteksi Zat Polutan (Boraks) di Desa Bongkasa-Bali - Esati, Ni Ketut (LPPPM STAI Darul Hikmah Bangkalan, 2023)
The activity of community service in Bongkasa Village, Bali was themed the counseling on turmeric (Curcuma domestica Val.) and water henna plants (Impatiens balsamina L.) as indicator to detecting pollutant substances (borax). The activity targeted young people who were members of Seka Teruna Teruni (STT) Banjar Tanggayuda. This activity was carried out in Bongkasa Village, seeing that the abundance of the plant was very much planted by the villagers. The content of chemical compounds in turmeric rhizome and henna flowers could react with borax to form a colored complex, so that these properties could be used to detect the presence of borax in food. It was known that economic problems caused producers to be irresponsible by adding borax as a food preservative, which is actually prohibited. Borax was a chemical compound derived from the heavy metal boron which generally was used as an antiseptic and bacteria killer, if used as a food additive it could endanger the health of consumers. The activity began with giving the questions to measure the knowledge of the counseling participants, then providing material, demonstrating the manufacture of a borax detector, as well as testing the detector on foods containing borax. Finally, an evaluation of the activity was carried out. The results obtained from this activity that the extension participants were very enthusiastic, this education was expected to add information to the public that there is a simple way to find out if a food contains the dangerous compound borax.